Spin–phonon coupling and thermodynamic behaviour in YCrO3 and LaCrO3: inelastic neutron scattering and lattice dynamics. (23rd September 2020) - Gupta, Mayanak K; Mittal, Ranjan; Mishra, Sanjay K; Goel, Prabhatasree; Singh, Baltej; Rols, Stephane; Chaplot, Samrath L
Abstract: We report detailed temperature-dependent inelastic neutron scattering and ab initio lattice dynamics investigation of magnetic perovskites YCrO3 and LaCrO3 . The magnetic neutron scattering from the Cr ions exhibits significant changes with temperature and dominates at low momentum transfer regime. Ab initio calculations performed including magnetic interactions show that the effect of magnetic interactions is very significant on the low- as well as high-energy phonon modes. We have also shown that the inelastic neutron spectrum of YCrO3 mimics the magnon spectrum from a G-type antiferromagnetic system, which is consistent with previously reported magnetic structure in the compound. The pressure-dependent ab initio lattice dynamics calculations are used to calculate the anisotropic thermal expansion behaviour in orthorhombic YCrO3, which is in excellent agreement with the available experimental data in the paramagnetic phase. We identify that the low energy anharmonic phonon modes involving Y vibrations contribute maximum to the thermal expansion behaviour.